Kinetics Approach of Biodegradation of Petroleum Contaminated Soil by using Indigenous Isolated Bacteria - Yudono, Bambang; Said, Muhammad; Sabaruddin, .; Napoleon, Adipati; Fanani, Zainal (JOURNAL OF TROPICAL SOILS, 2011)
The bioremediation of petroleum contaminated soil was investigated using a microscale Landfarming. The Indigenousbacteria, Pseudomonas pseudoalcaligenes, Bacillus megaterium, and Xanthobacter autotrophicus were isolated from the contaminated sites Sungai Lilin Jambi Pertamina Ltd and used further in the bioremediation experiments. The biodegradation rates of petroleum contaminated soil in the presence of the isolated bacteria were studied by using the chemical kinetics approach. The reaction orders were studied by using the differential method and the reaction rate constants were studied by using the integral method. The results showed that the reaction orders were 1.0949, 1.3985, 0.8823, and the reaction rate constants were 0.0189, 0.0204, 0.0324 day-1, respectively. Considering the values of reaction orders and reaction rate constants, the biodegradation rate of contaminated soil by usingeach bacteria had significantly different value; Xanthobacter Autotrophicus bacteria could degrade the petroleumoil sludge fastest than the others.Keywords: Biodegradation, indigenous bacteria, kinetics, petroleum oil